Genre & Politics - Fraim, John (New Explorations, 2025)
This essay argues that America’s political and cultural landscape is fundamentally shaped by the two archetypal symbols of Freedom and Equality, which correspond to masculine and feminine, Republican and Democratic, and individualistic versus communal worldviews. John Fraim suggests that these symbols are not merely political ideologies but deep psychological forces that structure the stories we tell and consume.Drawing on Marshall McLuhan’s “the medium is the message,” Fraim reframes genre as the hidden medium of political communication. Genres—such as Westerns, romances, thrillers, and fantasies—act as symbolic containers that naturally align with either Freedom or EqualityThe paper calls for a more conscious application of genre knowledge in political messaging, proposing that successful persuasion depends not only on content but on aligning that content with the appropriate narrative form in the context of the event. By understanding which genres best symbolize Freedom or Equality, communicators can craft stories that resonate with target audiences, transcend partisan divides, and potentially unite competing symbols into new hybrid narratives. The essay bridges screenwriting theory, symbolic analysis, and political communication, offering a fresh lens through which to view the stories that define—and could redefine—American culture.narratives. Using John Truby’s genre theory from The Anatomy of Genres, the leading authority on story genresFraim illustrates how different film genres express distinct worldviews and life philosophies, which can be strategically employed—or blended—to communicate political ideas effectively. Everyone says it’s about battle of genders today but it is really about a battle of story genres based around Freedom and Equality.